Sustainable IT playbook for technology leaders : design and implement sustainable IT practices and unlock sustainable business opportunities. - Sundberg, Niklas (Packt Publishing Ltd, 2022)
At a critical point in human history, this book presents proven ways to gain the skills needed to develop sustainable IT practices and set yourself apart as a progressive technology leader Key Features Execute a sustainable IT strategy with proven methods and real-world use cases Progress as a sustainable IT advocate and set yourself apart from other senior IT leaders Increase your chances of receiving executive buy-in on your sustainable IT strategy Book Description We are at a critical point in human history. Humanity is under threat, but all is not lost. We can take action! But how? Sustainable IT Playbook for Technology Leaders will show you how. It will walk you through the construction and implementation of a sustainable IT strategy and enable you to do your bit for the future of mankind. The book is split into three parts. Part I details the "why" and the clear and present danger that humanity faces today: the climate crisis. How did we get here, what are the immediate threats, what are the planetary boundaries that we need to peel back to safe levels, and what impact does IT have on society at large? Part II will focus on the "what." It examines the nitty-gritty details of what we can do to unlock significant returns on sustainable investments toward a more sustainable future. Part III, the final part of the book, focuses on the "how." How do you turn your ideas into action? What do you need to do to establish your baseline and your direction of travel towards your objective? This part provides tangible case studies and explains how you can start your journey today to begin delivering global and impactful objectives. By the end of this book, you'll be able to plan, implement, and communicate a sustainable IT strategy and set yourself apart as a progressive technology leader. What you will learn Discover why IT is a major contributor to carbon emissions Explore the principles and key methods of sustainable IT practices Build a robust, sustainable IT strategy based on proven methods Optimize and rationalize your code to consume fewer resources Understand your energy consumption patterns Apply a circular approach to the IT hardware life cycle Establish your sustainable IT baseline Inspire and engage employees, customers, and stakeholders Who this book is for This book is for executive IT leaders such as CIOs, CDOs, and CTOs dedicated to influencing, inspiring, and engaging businesses, organizations, and individuals to reduce their carbon footprint through sustainable IT practices.